Effect of Storage Methods on Various Sorts of Siberian Turnip (Brassica rapa L.) - Stepanova Alla G.; Davydenko Nataliia I.; Golub Olga V.; Stepanova Elena N. (Техника и технология пищевых производств)
Introduction. Vegetables are an integral part of human diet. Specialists from many countries of the world develop and improve technologies for storing vegetables in order to ensure the safety, quality, and quantity of commercial products. Turnip is one of the most promising vegetables from the point of view of healthy nutrition. Its production has been revived in recent years. This root vegetable has a high nutritional value and contains a significant amount of physiologically active components. There are regulatory documents for the storage of potatoes, carrots, and cabbage. However, storage standards for turnip are still under development due to the variability of their chemical composition, place of growth, etc. As a result, any rationale for storage methods for fresh and ripened turnips of different varieties grown on farms in the Novosibirsk region is relevant. Study objects and methods. The research featured fresh and ripened turnips of the «Kometa», «Luna», and «Orbita» varieties. Research methods were generally accepted and standard. The samples were stored at 0–1°C and relative humidity of 90–95% on pallets in opened plastic bags, board boxes with plastic liners, and board boxes without liners. Results and discussion. After 6 months, the method with polymer materials showed the best results, regardless of the variety: the average yield of quality products was 88%. Storage in wooden boxes without plastic liners provided only 70% of standard products. The decrease in the mass during 6-month storage was about 2% when stored in opened plastic bags and board boxes with plastic liners, while in board boxes without liners it was 20.6%. After the latter storage method, 9.8% of root crops appeared affected by microbiological diseases. A similar trend was observed in the content of total sugars: an average loss of 2.7% was detected when using polymer materials and 3.6% – without them. The board boxes with plastic liners proved better in preserving vitamin C: the average loss was 22.3%, while it reached 30.3% for plastic bags and 37.3% for board boxes without liners. After 6 months of storage, all samples maintained satisfactory quality. The sensory properties ranged from 7.01 to 7.94 points. The points were discarded for decreased consistency of epithelial tissues, pulp, taste, and aroma. Conclusion. The turnips of the «Kometa», «Luna», and «Orbita» varieties grown in the Novosibirsk region should be stored at 0–1°C and a relative humidity of 90–95% in plastic bags or board boxes with plastic liners placed on pallets.